Kajian Ketepatan Waktu Pelayanan pada Area Check-In Counter Terminal Domestik di Bandar Udara Internasional I Gusti Ngurah Rai Bali - Prasetya, Yudha Adi; Amir, Elfi; Purwaningtyas, Dian Anggraini (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
Check-in service is the initial stage of passenger departure that plays a critical role in the smooth operation of airport terminals. This study aims to assess the timeliness of passenger service at the check-in counter area of the Domestic Terminal at I Gusti Ngurah Rai International Airport, Bali, and to evaluate whether the service provided meets the standards set by the Indonesian Ministry of Transportation Regulation No. PM 30 of 2021, which states a maximum service time of 2 minutes and 30 seconds per passenger. This research employs a descriptive quantitative method through direct observation of 120 passengers across eight domestic airlines. The results show that the average check-in service time is 161.48 seconds, with a standard deviation of 51.5 seconds, indicating that the service exceeds the stipulated time standard. Contributing factors include an insufficient number of active counters, limited staff, and suboptimal utilization of self check-in technology. The study recommends the implementation of self baggage drop facilities to enhance service efficiency and reduce queuing times. Successful implementation of this technology requires passenger education, user-friendly machine interfaces, and the presence of assisting personnel to ensure smooth operations.